The effect of explicit instruction on the acquisition of subject-verb inversion by Macedonian learners of English - Stojanovska-Ilievska, Nataša (Linguistica Pragensia, 2023)
This paper reports on the effectiveness of teaching grammar explicitly, with a focus on form, function, and rules. The study tested the hypothesis that explicit instruction of grammar leads to increased accuracy in the grammaticality judgment, using a sample of 32 Macedonian learners of English at levels B and C. The structures selected for the task included subject-verb inversion, subject-verb inversion and it-insertion, omission of expletive and anticipatory it and omission of a referential subject, which are typical in the interlanguage of Macedonian learners of English due to cross-linguistic influence from their mother tongue and developmental factors. The study involved a pre-test, explicit instruction and controlled practice activities, and a post-test. The pre-test and post-test assessed the accuracy of a series of sentences, while the instruction involved contrastive analysis of examples in Macedonian and English, eliciting differences between the two languages. Results showed improved accuracy in the assessment of the grammaticality of the target structure at the post-test, but an experimental study with a control group is required to verify whether the improvement can be solely attributed to explicit instruction.